Предмет: Алгебра,
автор: MrWeksel
Упростите выражение
а)(8а-b)²-64a²=
Б)а(4-а)+(4-а)²=
Ответы
Автор ответа:
3
а) =64а^2-16ab+b^2-64a^2=-b*(16a-b)
б) =4a-a^2+16-8a+a^2=-4*(a-4)
б) =4a-a^2+16-8a+a^2=-4*(a-4)
Автор ответа:
3
а)(8a−b)^2−64a^2= 64a^2−16ab+b^2−64a^2=−16ab+b^2;
б)a(4−a)+(4−a)^2= a4 − a^2+16−8a+a^2=−4a+16
б)a(4−a)+(4−a)^2= a4 − a^2+16−8a+a^2=−4a+16
Похожие вопросы
Предмет: Русский язык,
автор: abdievaaman
Предмет: Физика,
автор: lovais04
Предмет: Українська мова,
автор: maksympolishchuk0206
Предмет: Химия,
автор: Ekaterina1719
Предмет: Математика,
автор: signal290803